2016
DOI: 10.1111/anu.12416
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic bacteria may prevent haemorrhagic septicaemia by maturing intestinal host defences in Brazilian native surubins

Abstract: The farming of hybrid surubins in Brazil has been affected by bacterial diseases. To avoid this problem, the development of prophylactics such as probiotics has proved to be a promising tool against bacterial outbreaks. This study evaluated the dietary supplementation with lactic acid bacterium Weissella cibaria and its probiotic action in the intestinal tract focusing the hemato‐immunological parameters, histology and electron microscopy. A total of 96 fish were maintained in a recirculation system and divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
(73 reference statements)
1
11
1
Order By: Relevance
“…The results of the present study corroborate with the results found by Jesus et al. (), that the probiotic may have induced an increase of the thrombocytes production, which can be interesting since these cells have important functions in fish immune system.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study corroborate with the results found by Jesus et al. (), that the probiotic may have induced an increase of the thrombocytes production, which can be interesting since these cells have important functions in fish immune system.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, no histomorphometric difference was observed in fish that received probiotic bacteria in diets when compared with fish that received the control diet. This outcome is contrary to that of Jesus et al (), who observed higher width, height, number of villi, and numbers of goblet cells in hybrid surubim ( Pseudoplatystoma reticulatum × P. corruscans ) after receiving the probiotic W. cibaria for 45 days. Other studies have reported higher measurements of gut metrics in fish that received probiotic bacteria, for example, Lee et al () in Anguilla japonica after 60 days of experiment and Abid et al () in Salmon salar after 63 days of feeding with probiotic bacteria.…”
Section: Discussioncontrasting
confidence: 99%
“…The increased PER of fish fed diets containing probiotic bacteria was influenced by the capacity of these microorganisms of increasing intestinal absorption surface, stimulating and producing compounds that improve digestibility, nutrients retention, protein use and energetic targeting (El‐Haroun et al., 2006), generating higher rates of protein efficiency and increased absorption areas in the intestines, as observed in this study. In addition, Bacillus have the capacity of producing enzymes that increases mineral availability (Jesus et al., 2016) and reduces anti‐nutritional factors of plant ingredients of diets, maximizing nutrients use (Cheng et al., 2012).…”
Section: Discussionmentioning
confidence: 99%